Maternal rodent exposure to di‐(2‐ethylhexyl) phthalate decreases muscle mass in the offspring by increasing myostatin. Issue 6 (19th October 2022) - Li, Fengju; Luo, Ting; Rong, Honghui; Lu, Lu; Zhang, Ling; Zheng, Chuanfeng; Yi, Dali; Peng, Yi; Lei, Enyu; Xiong, Xiaotao; Wang, Fengchao; Garcia, Jose M.; et al.
Abstract: Background: Di‐(2‐ethylhexyl) phthalate (DEHP) and its metabolites can cross the placenta and may cause birth defects and developmental disorders. However, whether maternal DEHP exposure affects skeletal muscle development in the offspring and the pathways involved are unknown. This study investigated the effects of maternal DEHP exposure and the contribution of myostatin (MSTN) to skeletal muscle development in the offspring. Methods: Pregnant wild‐type and muscle‐specific myostatin knockout (MSTN KO) C57BL/6 mice were randomized to receive vehicle (corn oil) or 250 mg/kg DEHP by gavage every other day until their pups were weaned (postnatal day 21 [PND21]). Body weights of the offspring mice were measured longitudinally, and their hindleg muscles were harvested at PD21. Also, C2C12 cells were treated with mono‐2‐ethylhexyl phthalate (MEHP), the primary metabolite of DEHP, and proteolysis, protein synthesis, and myogenesis markers were measured. The contribution of myostatin to maternal DEHP exposure‐induced muscle wasting in the offspring was determined. Results: Maternal DEHP exposure reduced body weight growth, myofibre size, and muscle mass in the offspring compared to controls (Quad: 2.70 ± 0.1 vs. 3.38 ± 0.23, Gastroc: 2.29 ± 0.09 vs. 2.81 ± 0.14, Tibialis: 1.01 ± 0.07 vs. 1.25 ± 0.11, mg/tibial length in mm, all P  < 0.01, n  = 35). Maternal DEHP exposure significantly increased Myostatin expression (2.45 ± 0.41 vs. 0.03 ± 0.00 DEHP vs. controls, P  < 0.01, n  = 5), Atrogin‐1(2.68 ± 0.65 vs. 0.63 ± 0.01, P  < 0.05, n  = 5), MuRF1 (1.56 ± 0.51 vs. 0.31 ± 0.01, P  < 0.05, n  = 5), and Smad2/3 phosphorylation (4.12 ± 0.35 vs. 0.49 ± 0.18, P  < 0.05), and decreased MyoD (0.27 ± 0.01 vs. 1.52 ± 0.01, P  < 0.05, n  = 5), Myogenin (0.25 ± 0.03 vs. 1.95 ± 0.56, P  < 0.05, n  = 5), and AKT phosphorylation (4.12 ± 0.35 vs. 1.00 ± 0.06, P  < 0.05, n  = 5), in skeletal muscle of the offspring in MSTN flox/flox, but not in MSTN KO mice. Maternal DEHP exposure resulted in up‐regulation of CCAAT/enhancer‐binding protein δ (C/EBPδ, 4.12 ± 0.35 vs. 1.00 ± 0.19, P  < 0.05, n  = 5) in skeletal muscle of the offspring in MSTN flox/flox and MSTN KO mice (4.12 ± 0.35 vs. 4.35 ± 0.28, P  > 0.05, n  = 5). In vitro, C/EBPδ silencing abrogated the MEHP‐induced increases in Myostatin, MuRF‐1, and Atrogin‐1 and decreases in MyoD and Myogenin expression. Conclusions: Maternal DEHP exposure impairs skeletal muscle development in the offspring by enhancing the C/EBPδ‐myostatin pathway in mice.